Words and Pictures: Back to basics for effective learning in the health sciences - Thunders, Dr Michelle; Jing, Ying; Clarke, Jim; Wadsworth, Dan; Thomas, Judy; Page, Rachel (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Students often struggle with science content because of their lack of science vocabulary comprehension and the general bewilderment with facing lengthy segments of text without meaning. This paper reports on a two pronged initiative to facilitate health science learning for first year degree students.Firstly, the introduction of visual diagrams into teaching practice. These diagrams summarize linkages between content and are valuable tools for visual learners and an important learning skill to develop for students new to the tertiary education environment. Secondly development of an online science vocabulary tool. Science vocabulary is often derived from Greek and Latin words, languages not familiar to the majority of our students. Knowing common suffixes, prefixes and root words can facilitate student understanding of new complex concepts. Development of a visual, interactive and quick online tool to aid students dissect and decode parts of words and help them to understand the entire word. This is particularly beneficial for students otherwise disadvantaged, for example, students where English is not their first language and students with little or no previous science education as often the case for students undertaking the Bachelor Health Science (BHlthSci) degree. This could also help with first-year student retention as it may help students to not see science words as daunting and confusing and give them confidence in their learning. Preliminary survey results indicate a positive student response to the initiatives with the majority of students using these tools to focus their revision and incorporating them in their self-directed learning.